1996
DOI: 10.1007/bf02446587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leukemia inhibitory factor on hemopoietic and stromal precursor cells in prolonged culture of mouse bone marrow

Abstract: Treatment of prolonged bone marrow cultures with leukemia inhibitory factor during the first 2 weeks after explantation has no appreciable effect on the production of precursors and mature hemopoietic ceils during 4 weeks of culturing. However, the proliferative potential of polypotent hemopoietic precursors in these cultures increases substantially. The addition of exogenous cytokine has a pronounced effect on the hemopoietic stroma, specifically, on the content of osteogenic precursors and ceils transporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Such variations have been observed in a murine heterotopic calcification model, 64 where LIF and OSM increased the number of bone-marrow stromal cell progenitors with osteogenic potential. 65 In this model, both cytokines induced an immature state of the mineral deposited on the extracellular matrix, as revealed by the presence of environment rich in labile non-apatitic phosphate, carbonate and HPO 4 . 66 Similar results have been obtained in in vitro rat bone-marrow stromal cell cultures.…”
Section: Leukaemia Inhibitory Factor (Lif) Oncostatin M (Osm) and Bomentioning
confidence: 90%
“…Such variations have been observed in a murine heterotopic calcification model, 64 where LIF and OSM increased the number of bone-marrow stromal cell progenitors with osteogenic potential. 65 In this model, both cytokines induced an immature state of the mineral deposited on the extracellular matrix, as revealed by the presence of environment rich in labile non-apatitic phosphate, carbonate and HPO 4 . 66 Similar results have been obtained in in vitro rat bone-marrow stromal cell cultures.…”
Section: Leukaemia Inhibitory Factor (Lif) Oncostatin M (Osm) and Bomentioning
confidence: 90%
“…The approximate number of cells implanted was about 7-9 ϫ 10 6 cells according to Drize et al (22) Adherent monolayer cells were pooled with the nonadherent cells and washed three times with fresh culture medium. This cell pellet was then implanted under the renal capsule of 4-week-old female B6D2F1 mice according to the method of Friedenstein et al (24) The operations were performed under ketamine (Parke-Davis, Courbevoie, France) and xylazine (Bayer, Sens, France) anesthesia, and the bone marrow cells were implanted for 10 weeks (10 mice for each condition).…”
Section: Bone Marrow Cell Culture and Heterotopic Implantationmentioning
confidence: 99%
“…The effects of LIF on hematopoietic and bone marrow stromal precursor levels in osteoblast cells have recently been investigated in the formation of murine ectopic calcification. (22) These investigations showed that LIF stimulated the proliferation of stromal progenitors with osteogenic potential. Though LIF increased the size and weight of bone shell formed under the kidney capsule, the qualitative characteristics of the ectopic bone formed have not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation